Secondhand effects of alcohol use: the consequences of peer drinking behavior - Boyle, Morgan A., author; Prince, Mark, advisor; Davalos, Deana, committee member; Riggs, Nathaniel, committee member (Colorado State University. Libraries, 2021)
Objective: College student alcohol misuse is a public health concern that negatively affects the individual using alcohol, and the individual's peers. The secondhand effects of alcohol use (SEA) are adverse consequences caused by another's drinking (i.e., study/sleep interrupted, being insulted or humiliation, sexual assault or rape). The present study explored SEAs relationship to personal alcohol, alcohol related consequences, and wellbeing. This study also investigated coping as a possible moderator for SEA. Method: 1,168 students were recruited from an undergraduate research pool. Participants completed a survey which assessed for SEA, wellbeing, personal use, alcohol related consequences, and coping strategies. Results: SEA was found to have a significant positive relationship with personal use for both heaviest day of drinking and AUDIT score as well as alcohol related consequences. Regarding coping, the present study found that higher levels of maladaptive coping strengthened the relationship between SEA and alcohol related consequences while adaptive coping did not significantly weaken this interaction. Conclusion: This study established a relationship between SEA and increased personal use as well as alcohol related consequences, a relationship which was strengthened by maladaptive coping. By establishing a connection between SEA and harmful behaviors I hope to increase understanding and awareness regarding the deleterious effects of SEA. In addition, it is hoped that these findings may inform intervention and treatment recommendations for those experiencing adverse outcomes due to SEA.